Human capital challenges in the hotel industry of Canada: finding innovative solutions. (14th August 2017) - Willie, Paul A.; Connor, David; Sole, Jordi; Forgacs, Gabor; Grieve, Robert; Mueller, Jennifer
Abstract : Purpose: This paper aims to identify possible solutions to the current and persistent challenge of attracting and retaining qualified people to work in Canada's hotel industry. The outlook for the industry is that a critical shortage of skilled workers will continue to exist for at least the next decade. Design/methodology/approach: This paper draws on the perspectives of three academics and three industry practitioners in an effort to identify root causes and possible solutions. Canadian and international literature is reviewed to establish current practices and point to gaps to be filled to meet the market needs. Recommendations are categorized by industry and academic perspectives. Findings: The Canadian hotel industry faces challenges in filling job vacancies and maintaining employees in their roles. It is important for industry and academia to work collaboratively to educate the general public on the rewards and benefits of working in the Canadian hotel industry. Practical implications: Many concrete strategies are suggested that individual hotel operations and the industry as a whole can implement to improve their human resource management and to entice potential employees to join the sector. Originality/value: This paper adds value and contributes to the Canadian hotel industry and academia, as it represents current research and thought processes from both the academic community and the Canadian hotel industry.